Visible Light as an Antimicrobial Strategy for Inactivation of Pseudomonas fluorescens and Staphylococcus epidermidis Biofilms - Valeria Angarano; Cindy Smet; Simen Akkermans; Charlotte Watt; Andre Chieffi; Jan F.M. Van Impe (MDPI AG, 2020)
The increase of antimicrobial resistance is challenging the scientific community to find solutions to eradicate bacteria, specifically biofilms. Light-Emitting Diodes (LED) represent an alternative way to tackle this problem in the presence of endogenous or exogenous photosensitizers. This work adds to a growing body of research on photodynamic inactivation using visible light against biofilms. Violet (400 nm), blue (420 nm), green (570 nm), yellow (584 nm) and red (698 nm) LEDs were used against Pseudomonas fluorescens and Staphylococcus epidermidis. Biofilms, grown on a polystyrene surface, were irradiated for 4 h. Different irradiance levels were investigated (2.5%, 25%, 50% and 100% of the maximum irradiance). Surviving cells were quantified and the inactivation kinetic parameters were estimated. Violet light could successfully inactivate P. fluorescens and S. epidermidis (up to 6.80 and 3.69 log10 reduction, respectively), while blue light was effective only against P. fluorescens (100% of maximum irradiance). Green, yellow and red irradiation neither increased nor reduced the biofilm cell density. This is the first research to test five different wavelengths (each with three intensities) in the visible spectrum against Gram-positive and Gram-negative biofilms. It provides a detailed study of the potential of visible light against biofilms of a different Gram-nature.